PENGARUH STRUKTUR MODAL, INFLASI, NILAI TUKAR TERHADAP RETURN SAHAM PERUSAHAAN PERBANKAN DI BEI TAHUN 2017-2021 - Riskiyani, Desi Nur; Dewi, Eka Kusuma (LPPM Universitas Putera Batam, 2023)
This study aims to examine the impact of capital structure, inflation, and exchange rates on stock returns in banking companies listed on the Indonesian Stock Exchange (IDX) during the period 2017-2021. It falls under the category of quantitative research, utilizing secondary data for collection. The population consists of banking companies listed on the IDX between 2017 and 2021, with sample selection conducted through purposive sampling, resulting in 17 banking companies and 85 observational data points. The analysis and hypothesis testing employed panel data regression analysis using Eviews-10. The findings from the regression analysis indicate that the capital structure and exchange rates, when considered individually, do not have a significant effect on stock returns. However, inflation, when examined separately, demonstrates a partial impact on stock returns. Moreover, when examining all variables simultaneously, including capital structure, inflation, and exchange rates, there is a significant collective effect on stock returns